Kampanye Sosial Pencegahan Fenomena Penipuan File.APK - Ayu Ramadia Sali; Dwi Mutia Sari (Lembaga Pengembangan Kinerja Dosen, 2023)
Technological developments are currently widely used by some people to commit cyber crimes, especially in this case using the .apk file. Android Package Kit / APK is an application format for Android-based smartphones. The number of victims arising from the phenomenon of file.apk fraud, so understandably there are still many who don't know about file.apk fraud. Therefore the designer makes a design for a media campaign as a means of preventing the phenomenon of file.apk fraud. The design method used is Design Thinking which is based on data obtained through questionnaires, documentation, and literature studies regarding the phenomenon of file.apk fraud. In the problem solving process, apply the 5W+1H analysis (what, who, when, why, where, and how). This design produces prevention media in the form of infographic posters.